Pengaruh Promo Gratis Ongkos Kirim, Kemudahan Pembayaran dan Kemudahan Penggunaan Terhadap Keputusan Pembelian pada Marketplace Shopee (Studi Kasus Mahasiswa Fakultas Ekonomi dan Bisnis Universitas Islam Malang 2019) - Alfi Septina; Nur Hidayati; Andi Normaladewi (UNIVERSITAS ISLAM MALANG, 2023)
Abstract This study aims to analyze the effect of free shipping promos, ease of payment, and ease of use on purchasing decisions. The population in this study were students of the Faculty of Economics and Business at the Islamic University of Malang class of 2019 and Shopee users. This research includes explanatory research with a quantitative approach. The sample used was purposive sampling with a sample size of 90 respondents. The data collection technique uses questionnaires through Google Form. The results of this study partially show that free shipping promos, ease of payment, and ease of use influence purchasing decisions. All independent variables simultaneously influence purchasing decisions. Keywords: free shipping promos, ease of payment, ease of use, on purchase decisions